PROGRAM AKRASA KATA SERABI: SENIN READ ALOUD BERCERITA - Amanda Salsabilla; Meci Watul Haria; Nasrul Asmawan; Rahmat Kurniawan (STKIP Subang, 2025)
his report describes the implementation of the SERABI program (Senin Read Aloud dan Bercerita) as a school literacy initiative integrating artificial intelligence to support students’ reading and storytelling skills. The program was developed in response to students’ limited reading fluency, storytelling ability, and confidence in oral expression. The objective of the program is to foster reading aloud skills, storytelling competence, creativity, critical thinking, and digital literacy through enjoyable and routine literacy activities. The program was implemented using a descriptive approach through weekly activities conducted every Monday for 15–20 minutes, including reading aloud AI-generated stories, storytelling, digital story creation using Gemini AI, and guided discussions. The results show positive outcomes, including improved reading fluency, more expressive storytelling, increased student confidence, higher motivation to read, and active participation in literacy activities. The SERABI program also strengthens the school’s literacy culture and promotes responsible and productive use of digital technology in